Importance of Mizaj and Nutrition in Treating Adolescent Aggression (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Aggression in adolescents is a current problem related to psycho-emotional state and physiological factors. The concept of mizaj in traditional medicine suggests that individual temperament influences behavioral responses. Diet also plays an important role in regulating the nervous system.Objective: To examine the impact of Mizaj temperament on aggression and gastrointestinal dysfunction, with a focus on dietary preferences based on Unani medicine principles.Methods: 212 adolescents (13.5-14.8 years old) were analyzed. Mizaj assessment by traditional diagnosis, analysis of aggression by Buss-Durkee scale, study of dietary habitsResults: Correlations between mizaj, diet and level of aggression were determined. Adolescents with a particular type of mizaj (e.g., saffravium or damavium) showed increased rates of aggression, especially with magnesium, vitamin D, and omega-3 deficiencies.Conclusion: Nutritional correction and consideration of mizaj can reduce aggression in adolescents, which can be used in prevention programs.